Neuromuscular disorders - Tawil, Rabi N.; Venance, Shannon Lee, 1959- (Chichester, West Sussex, UK : Wiley-Blackwell, 2011)
A new addition to the Neurology in Practice series, Neuromuscular Disorders provides a clinical guide to the challenging diagnosis and management of neuromuscular disorders. As a part of the series, various feature boxes are highlighted throughout. "Tips and Tricks" give suggestions on how to improve outcomes through practical technique or patient questioning. In addition, "Caution" warning boxes supply helpful advice on how to avoid problems and 'Science Revisited' boxes offer quick reminders of the basic science principles necessary for understanding the presented concepts.
Neuromuscular Disorders; Contents; Contributor List; Acknowledgment; Series Preface; Preface; 1: Neuromuscular Diseases: Approach to Clinical Diagnosis; Part I: Myopathies; 2: Approach to Diseases of Muscle; 3: Inflammatory Myopathies; 4: Toxic Myopathies; 5: Metabolic Myopathies; 6: Mitochondrial Myopathies; 7: Dystrophinopathies; 8: Limb-Girdle Dystrophies; 9: Facioscapulohumeral Dystrophy; 10: Myotonic Dystrophies; 11: Oculopharyngeal Muscular Dystrophy; 12: Distal Myopathies; 13: Muscle Channelopathies; 14: Congenital Myopathies; Part II: Disorders of the Neuromuscular Junction.
Includes bibliographical references and index.
Print version record.
Keywords: Neuromuscular diseases; HEALTH & FITNESS -- Diseases -- Musculoskeletal; MEDICAL -- Orthopedics; MEDICAL -- Rheumatology; Neuromuscular diseases; Neuromuscular Diseases -- diagnosis; Neuromuscular Diseases -- therapy; Electronic books; Electronic books